Eletrofiação da quitosana e sua aplicação como curativo para feridas - Scheidt, Desiree Tamara (2018)
Nanofibers generated using polymers are generally produced by the electrospinning method. It is a simple, economical and versatile technique that uses an electric force to generate ultrafine fibers. Chitosan is a non-toxic, biodegradable, biocompatible polymer obtained from renewable natural sources that attracts the interest of researchers. However, due to the difficulty of electrospinning pure chitosan, it has been tried to ally the poly (ethylene oxide) PEO to the polymeric matrix of chitosan, in order to facilitate the process of obtaining fibers. In this context, the initial objective of this work was to obtain a polymeric blends containing chitosan and PEO capable of generating nanofibers when subjected to the electrospinning process. The poly (ethylene oxide) was excellent as a helper in chitosan spinning, allowing the obtaining of fibers with up to 90% of the same and the average diameter obtained was of 320nm. The process parameters were evaluated and the ones that showed the best result were a concentration of 4% of chitosan and 2% of PEO, applied tension of 18kv and distance between the collector and needle of 20cm. The incorporation of PEO into the polymeric matrix of chitosan proved to be an effective strategy for obtaining nanofibers by the electrophilic process. The study was then carried out for the incorporation of the drug neomycin sulfate into the electrophilic matrix. Membranes in the ratio of 90/10 (v / v) chitosan / 4% PEO / 4% (m / v), as well as membranes in the ratio 80/20 (v / v) chitosan / PEO (4% / 2%) were studied as support for the incorporation of the drug. When the neomycin sulfate was incorporated together with the solution and subjected to electrospinning, the diameter of the fibers obtained were even smaller, with a mean of 258nm. The obtained membranes were subjected to physico-chemical analysis, which proved the miscibility of the polymers chitosan and PEO as well as confirmed the incorporation of the neomycin sulfate to the blend. The antimicrobial activity for the drug and non-drug membranes was investigated against Gram positive and Gram negative bacteria and the registered inhibition halos were larger or near the control. The neomycin sulfate release test indicated that it had a rapid release profile, and with only 120 minutes, much of the drug had already been released from the polymer film. In view of this, the membranes developed in this study suggest to be promising candidates for the application as a biomaterial in wound healing.